2016
DOI: 10.1139/cjas-2015-0125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milk fat to protein ratio on genetic variance for milk yield in Thai tropical Holstein cattle

Abstract: The objective of this research was to investigate the optimum fat to protein ratio (FPR) in Thai tropical Holstein dairy cattle. First parity data consisting of 20 492 milk yields (MY) records for 24 891 cows for the period 2001 and 2011, were used in the analysis. The analysis used a random regression test-day animal model of thirdorder Legendre polynomials through the creation of a covariance function based on different FPRs. Variance components were estimated using the Bayesian method via the Gibbs sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…In this study, the means were within the ranges reported in previous studies in Thailand. (Buaban et al, 2016;Puangdee et al, 2016;Wongpom et al, 2017) and similarly the result from Satola and Ptak (2019) in Polish HF.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this study, the means were within the ranges reported in previous studies in Thailand. (Buaban et al, 2016;Puangdee et al, 2016;Wongpom et al, 2017) and similarly the result from Satola and Ptak (2019) in Polish HF.…”
Section: Discussionsupporting
confidence: 81%
“…In Thailand, there are several report and investigate the topic of FPR in Thai tropical Holstein dairy cattle. Puangdee et al (2016) Buaban et al (2016) Puangdee et al (2017. In the study of Buttchereit et al (2011) examining the genetic relationship between daily energy balance and FPR it was shown that the correlation was high at the beginning of lactation and decreased toward zero at 180 DIM.…”
Section: Introductionmentioning
confidence: 99%